171 Right ventricular free wall longitudinal strain (RVFWSL): a new outcome predictor in patients candidate for TAVI. (8th December 2021) - Dellino, Carlo Maria; Pergola, Valeria; Torresan, Frnacesca; Baroni, Giulia; Cecchetto, Antonella; Aruta, Patrizia; Fiorencis, Andrea; Fraccaro, Chiara; Tarantini, Giuseppe; Mele, Donato; Iliceto, Sabino
Abstract: Aims: Right ventricular systolic dysfunction is considered an outcome predictor in various cardiac diseases, sometimes stronger than ejection fraction (EF). We assume that right ventricular dysfunction, calculated with echocardiography in patients candidate for trans-catheter aortic valve implantation (TAVI), could be an outcome predictor. To evaluate the prognostic value of pre-TAVI right ventricular free wall longitudinal strain (RVFWSL) in patients with severe aortic stenosis undergoing TAVI. Methods and results: Retrospective analysis of 100 patients underwent transfemoral TAVI in our hospital from January 2015 to September 2019, with at least a pre-TAVI and post-TAVI echocardiography. For each patients we collected clinical and echo data before and after TAVI and during the follow-up; we measured RVFWSL off-line at the same time. We considered the value of [23.3]% the cut-off of normality for RVFWSL. The primary endpoint was a composite of death from any cause and hospitalization for heart failure. The median age of the patients was 81 years (79–83) and EF was preserved in most patients (median: 56%, 55–58.28%). At a median follow-up of 1023 days (630–1387), the univariate analysis demonstrated a predictive of a reduced RVFWSL before TAVI ( < [23.3]%, P  = 0.015) and EF < 50% ( P  = 0.014). Cox regression analysis found that pre-TAVI reduced RVFWSL (HR: 2.875, CI 95%: 1.113–7.425; P  = 0.03) and EF < 50% (HR: 2.511, CI 95%: 1.07–5.892; P  = 0.03) were independently associated with composite endpoint of the study. Moreover, a reduced EF associated with RVFWSL < [23.3]% had an incremental value in predicting the outcome ( P  = 0.021). Conclusions: Among patients with severe aortic stenosis undergoing TAVI, a reduced pre-implant RVFWSL is able to predict long-term outcome.